2006
DOI: 10.1124/jpet.106.103960
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Orphanin FQ/Nociceptin Is Involved in the Development of Morphine Tolerance

Abstract: The neuropeptide orphanin FQ/nociceptin (OFQ/N) has been shown to counteract several effects of endogenous and exogenous opioids, and it has been proposed as an opioid-modulating agent involved in the development of morphine tolerance and dependence. However, conflicting results have been obtained from animal models using different protocols to induce morphine tolerance. Here, we report that both genetic and pharmacological blockade of OFQ/N signaling can effectively prevent development of morphine tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…In support of these findings, it is notable that previous studies have shown that both NOP receptor KO (Ueda et al, 2000) and N/OFQ precursor KO (Chung et al, 2006) mice fail to develop tolerance to chronic morphine administration. Similar results are seen following administration of the NOP receptor antagonists (Zaratin et al, 2004;Chung et al, 2006).…”
Section: Endogenous N/ofq and The Plastic Changes That Underlie The Csupporting
confidence: 71%
See 1 more Smart Citation
“…In support of these findings, it is notable that previous studies have shown that both NOP receptor KO (Ueda et al, 2000) and N/OFQ precursor KO (Chung et al, 2006) mice fail to develop tolerance to chronic morphine administration. Similar results are seen following administration of the NOP receptor antagonists (Zaratin et al, 2004;Chung et al, 2006).…”
Section: Endogenous N/ofq and The Plastic Changes That Underlie The Csupporting
confidence: 71%
“…Similar results are seen following administration of the NOP receptor antagonists (Zaratin et al, 2004;Chung et al, 2006). Additionally, mice with null mutations of the N/OFQ gene adapt poorly to repeated stress (Koster et al, 1999).…”
Section: Endogenous N/ofq and The Plastic Changes That Underlie The Csupporting
confidence: 66%
“…Thus, we next investigated the effect of pretreatment with the selective ORL1 antagonist J-113397 on 030418 tolerance. The experimental results suggested that pharmacological blockade with J-113397 significantly prevented analgesic tolerance to morphine on d 7, which confirms earlier findings [30,31] . In contrast, pretreatment with J-113397 could not effectively alter the development of tolerance to 030418.…”
Section: Discussionsupporting
confidence: 80%
“…Many previous studies have used high doses of opioid drugs to induce and study tolerance [27,30,31] . As expected, repeated treatment with morphine (30 mg/kg, sc, thrice daily) induced the rapid development of analgesic tolerance.…”
Section: Development Of 030418 Tolerance and The Effect Of Pretreatmementioning
confidence: 99%
“…Enhanced activities of anti-opioid neurons are suggested to be involved in the development of tolerance to central morphine. There are several antiopioid neuronal systems in the central nervous system, such as cholecystokinin (34), neuropeptide FF (35), and nociceptin systems (36). Since a complicated neuronal network is not present in the peripheral nervous system, peripheral opioid analgesia may be resistant to the development of tolerance.…”
Section: Discussionmentioning
confidence: 99%